IMPLEMENTASI WEB SERVICES SISTEM INTEGRASI DATA MENGGUNAKAN TEKNIK REPLIKASI DATA PADA INVENTARISASI BANGUNAN PEMERINTAH - Ilhamsyah Ilhamsyah (SISFOTENIKA, 2011)
Abstracts: This system prototype displays a list of government data objects, buildings, projects, construction specifications, and recapitulation of building conditions in each city/regency server which provides URL service provider and service requestor. Web services technology enables the integration of application services from different systems that are at BPKAD Pontianak and Pontianak regency. The implementation of web service in data replication at server side will increase the speed when it is accessed. The research result of this web service is an appropriate infrastructure for the needs of data integration of buildings that are spread in each server of cities/regencies. The data integration which is built by using web service in the prototype data integration system can be used as a source of data and information to support the work of local government. Keywords: administration, inventory, web service, integration, data, n-tier, SOAP